The Unintended Consequence of Novel Coronavirus (COVID-19) Pandemic on Racial Inequities Associated With Adverse Childhood Experiences (ACEs): Findings From a Population-Based Study - Srivastav, Aditi; Richard, Chelsea L.; McRell, Amanda S.; Strompolis, Melissa (Frontiers in Public Health, 2021)
A rising concern is the COVID-19 pandemic effect on adverse childhood experiences (ACEs) due to increased parental stress and social/physical isolation. These pandemic effects are likely to be higher in already marginalized communities. The objective of this ecological study was to examine the relationship between COVID-19 cases and deaths, race/ethnicity, and the estimated number of adults with ACEs using data from South Carolina (SC). COVID-19 reported cases and death data were obtained from the SC Department of Health and Environmental Control. ACE data was used from the 2014–2016 SC Behavioral Risk Factor Surveillance System. Census data were used to obtain county population data. To measure the relationship between these variables, the Spearman rank-order correlation test was used because the data distribution was non-normal. There was a moderate relationship between the estimated number of adults with one or more ACEs and deaths (ρ = 0.89) and race/ethnicity-specific COVID-19 case counts by county (Black: ρ = 0.76; =White: ρ = 0.96; Hispanic: ρ = 0.89). Further, the Spearman correlation test showed the strongest relationship between COVID-19 deaths and race-ethnicity-specific county populations was with the Black adult population (ρ = 0.90). Given the known link between existing health inequities and exposure to COVID-19, these results demonstrate that the current pandemic could have unintended consequences on the well-being of children and caregivers. Response efforts should consider promoting protective factors for children and families and advocating for equitable policies and systems that serve children.